Stimulus on germination and initial development of maize cultivar AS 1820 with Stimullum® biostimulant - Netta, Maria Abadia de Souza; Menezes Filho, Antonio Carlos Pereira de; Batista-Ventura, Hellen Regina Fernandes; Andrade, Christiano Lima Lobo de; Ventura, Matheus Vinicius Abadia (Brazilian Journal of Science, 2022)
The present study aimed to evaluate the stimulus on germination and initial development via application of doses of the biostimulant Stimullum® in seeds in hybrid AS 1820 corn in the Cerrado of the State of Goiás, Brazil. The experiment was conducted in pots, in a greenhouse in Rio Verde, Goiás, Brazil, in the year 2022. The design used was completely randomized, in a factorial scheme with 5 doses and 4 replications. The application of Stimullum® biostimulant dosages was performed one hour before sowing (0, 100, 200, 300, 400 mL ha-1, 60,000 seeds-1). Germination, plant height, number of leaves, leaf length, leaf width, leaf area, root length, fresh and dry aerial mass, fresh and dry root mass, and chlorophyll a and b indices were evaluated. The biostimulant Stimullum® did not influence germination, shoot length, leaf number, leaf width, shoot fresh mass, shoot and root dry mass and chlorophyll content. However, the application of Stimullum® at a dose of 200 mL ha-1 showed significant increases in leaf length, leaf area, root length and root fresh matter at the beginning of the development of AS 1820 hybrid corn.